Comparison Of Wound Healing Process Between Hepar Sulph With Aloe Vera Wound Care Dressing Treatment Among Diabetic Foot Ulcers : A Pilot Study - Muslim, Dede Nur Aziz Muslim; FARIDAH MOHD SAID; NISHA NAMBIAR; NUR INTAN HAYATI HUSNUL KHOTIMAH; Yuyun Sarinengsih (Holistic Nursing Plus, 2025)
This pilot study examines the effectiveness of Hepar Sulph and Aloe Vera in diabetic foot ulcer management. Key findings indicate superior outcomes with Hepar Sulph in wound size reduction and closure time. Implications for alternative wound care strategies are discussed. Diabetic foot ulcers (DFUs) pose a significant challenge in diabetic patient management. This pilot study aims to compare the effectiveness of Hepar Sulph and Aloe Vera in promoting wound healing among diabetic foot ulcer patients. A total of 60 participants were divided into three groups: 20 in the control group treated with normal saline (NaCl), 20 in the Aloe Vera group, and 20 in the Hepar Sulph group. The study found that both Hepar Sulph and Aloe Vera were effective in wound healing, with Hepar Sulph demonstrating superior results. This study highlights the potential of Hepar Sulph as a more effective treatment option for DFUs compared to Aloe Vera.